Cell physiology sourcebook : a molecular approach - Sperelakis, Nick, 1930- (Academic Press, 2001)
This completely revised and updated source book provides comprehensive and authoritative coverage of cell physiology and membrane biophysics. Intended primarily as a text for advanced undergraduate and graduate students and as a reference for researchers, this multidisciplinary book includes several new chapters and is an invaluable aid to scientists interested in cell physiology, biophysics, cell biology, electrophysiology, and cell signaling. * Includes broad coverage of both animal and plant cells * Appendices review basics of the propagation of action potentials, electricity, and cable properties.